Outcome after curative resection of large (≥10 cm) gastric gastrointestinal stromal tumors: How frequent is adjacent organ involvement and is concomitant distal pancreatectomy necessary? - Goh, B.K.P. (2014)
10.1007/s11605-009-1083-4